Utilizing Technology to Encourage Marketing Of MSMES Based on Influencer Marketing Through The INNSIGHT Platform - Agustini, Dwi; Putri, Valda; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This research discusses the use of technology in marketing MSMEs through influencer marketing using the INNSIGHT platform. This study uses an integrative review method to analyze the SWOT literature and a qualitative descriptive analysis to understand the qualitative data. The results of the study show that INNSIGHT can make it easier for MSME players to promote their products through influencer marketing. However, this application also has weaknesses such as dependence on a stable internet network and limited resources. The opportunity that INNSIGHT has is to get a target market that fits the available influencer categories. The threat faced is the use of increasingly sophisticated technology by financial technology service providers. The INNSIGHT application can be downloaded on the Playstore and App-store, and has features such as a homepage, insight posts, chat, customer support team, endorsement packages.